Trade between China and the Netherlands: a Case Study of Globalization - Frank A.G. den Butter; Raphie Hayat (Tinbergen Institute, 2008)
During the last decades, the growth of trade between China and the Netherlands has been larger than the increase in bilateral trade flows between China and most other countries. Using a time series based gravity model, this paper investigates the main determinants of this increase. The empirical analysis indicates that, apart from GDP growth, Dutch in-house offshoring to China is a major determinant of Dutch import growth from China. Dutch firms tend to offshore production in-house when the asset specificity of the traded inputs is high and offshore via the market when this asset specificity is low. Controlling for these product types also reveals that transport costs are more important for trade in homogeneous and reference priced goods than for trade in differentiated goods
Keywords: F14; L16; L23; 330; international trade; transaction costs; offshoring; foreign direct investments; asset specificity; gravity model; Internationale Wirtschaftsbeziehungen; Transaktionskosten; Auslandsverlagerung; Auslandsinvestition; Gravitationsmodell; China; Niederlande